2016
DOI: 10.1097/gme.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the trajectories of vasomotor symptoms across the menopausal transition

Abstract: Objective To investigate the heterogeneity of temporal patterns of vasomotor symptoms (VMS) over the menopausal transition and to identify factors associated with these patterns in a diverse sample of women. Methods The Study of Women's Health Across the Nation is a multi-site longitudinal study of women from five racial/ethnic groups transitioning through the menopause. The analytic sample included 1455 women with non-surgical menopause and a median follow-up of 15.4 years. Temporal patterns of VMS and asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 43 publications
5
82
1
Order By: Relevance
“…Although VMS can persist well beyond the FMP, perhaps at least as long as a decade (Avis et al, 2015; Tepper et al, 2016) and continue to be associated with sleep problems, variability in reproductive hormone concentrations (i.e., E2, FSH) do not share a similarly strong association with sleep complaints in midlife women. Freeman et al (2015) suggested that this lack of association could also be attributed to their analytic models, which included time relative to the FMP, which reflects changing hormone concentrations during the MT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although VMS can persist well beyond the FMP, perhaps at least as long as a decade (Avis et al, 2015; Tepper et al, 2016) and continue to be associated with sleep problems, variability in reproductive hormone concentrations (i.e., E2, FSH) do not share a similarly strong association with sleep complaints in midlife women. Freeman et al (2015) suggested that this lack of association could also be attributed to their analytic models, which included time relative to the FMP, which reflects changing hormone concentrations during the MT.…”
Section: Discussionmentioning
confidence: 99%
“…Use of group-based trajectory modeling accounted for heterogeneity within the sample, allowing us to identify groupings that are both statistically sound and scientifically valid (Tepper et al, 2016). Using the available premenopausal and postmenopausal observations and within-woman duration (i.e., time) we were able to evaluate sleep maintenance trajectories pre- and post-FMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to study the heterogeneity of temporal patterns of VMS, Tepple et al evaluated 1455 women with nonsurgical menopause over a median follow-up of 15.4 years and described four distinct trajectories: 'early onset' (onset about 11 years before the final menstrual period with decline after menopause), 'late onset' (onset near the final menstrual period with later decline), 'high frequency' (onset early with persistently high frequency) and 'low frequency' (persistently low frequency). In a further analysis, they found that relative to women with a persistently low frequency of VMS, women with persistently high-and early-onset VMS had a more adverse psychosocial and health profile (6). Of course, this begs the question as to what is cause and effect.…”
Section: Neural Mechanism: Wet Flushingmentioning
confidence: 99%
“…2 Physical symptom severity and changes in subjective measures of wellbeing may also be associated with age of onset of menopause, with earlier onset being associated with greater physical symptom severity and poorer psychosocial functioning. 4 Many areas of the brain related to aging may also be sensitive to changes in hormonal levels, with gonadal changes that occur around mid-life also being thought to be associated with changes in cognitive functioning. 5 Mood symptoms are known to be common throughout the menopause transition period.…”
Section: Introductionmentioning
confidence: 99%